The Influence of Financial Literacy on Interest in Investing for the Academic Community of Akademi Keuangan & Bisnis Indonesia Internasional (AKBII), Bandung, Indonesia - Hamka Hamka; Muhamad Jupri; Ruly Budiono (International Journal of Business, Economics, and Social Development, 2020)
This paper aims to analyze the effect of financial literacy on investment interests among academicians. The study was conducted on all four aspects of financial literacy, namely general knowledge of personal finance, savings and loans, insurance, and investment partially and simultaneously on investment decisions from lecturers, employees, and students at the Indonesian International Finance and Business Academy in Bandung. The subjects in this study were lecturers, employees, and active students majoring in management and accounting at the Indonesian International Finance and Business Academy in Bandung with a total number of 240 questionnaire respondents. The results of the analysis show that financial literacy has a strong influence on investment interests for the academics of the Bandung International Finance and Business Academy.